Valorisation of bioactive compounds from Bentong ginger (Zingiber officinale Roscoe var. Bentong) using ultrasound-assisted extraction - Again, V.; Kamaruddin, S. K.; Suleiman, Norhidayah (Universiti Putra Malaysia, 2022)
The present work demonstrated the bioactive compound recovery from Bentong ginger (Zingiber officinale Roscoe var. Bentong) using ultrasound-assisted extraction (UAE) in terms of crude yield (CY), as well as total phenolic content (TPC), 1,1-diphenyl-2-picrylhydrazyl (DPPH), and ferric reducing-antioxidant power (FRAP), which reflected the antioxidant properties. These response variables were evaluated as functions of the independent variables; temperature (30 - 60°C), time (10 - 30 min), and ultrasonic intensity (1768 - 5304.10 W/cm2 ), using response surface methodology (RSM). The variables were optimised using quadratic polynomial through the correlations calculated from the regression models fitted to the experimental data. The predicted values of CY, TPC, FRAP, and DPPH under the optimal conditions (40°C, 3536.78 W/cm2 , and 25 min) were 23.42%, 778.08 mg GAE/g, 636.08 µmol Fe2+/g, and 150.01%, respectively. These experimental values were well fitted with the predicted values, except for DPPH. With UAE set at the optimal conditions, a pre-leaching step (PLS) was added to the process to investigate its effect on the extraction. It was found that PLS-UAE produced higher extraction yields (30.15%); however, the antioxidant activity of the extracts was significantly (p < 0.05) higher at the optimised condition for UAE only treatment. The PLS application led to structural cell damage which increased CY, and this was validated through scanning electron microscopy (SEM).